Energy efficiency mechanism using mobile-based fermat's spiral in wireless sensor networks - Mantoro, Teddy; Shaukat Ali, Haroon; Ayu, Media Anugerah; Usino, Wendi (2011)
There are 2 well-known ways to optimize energy efficiency in wireless sensor networks (WSN). The first one is to deploy multiple sinks in wireless sensor networks to balance the energy consumption among the wireless sensor nodes. The second technique is to move the sink navigating through wireless sensor network to redirect traffic flow while gathering sensed data timely and efficiently. Both ways will try to reduce the famous bottleneck problem that cause wireless sensor nodes energy nearest to base station depleted very quickly. We evaluated the performance of wireless sensor network using minimum spanning tree algorithm specifically Prim’s Algorithm in order to know the bottleneck effect on wireless sensor network and propose a better solution performance based on Fermat Spiral model. We show that such a solution reduces the bottleneck problem, increases the energy efficiency of the network and produces greater data transmission throughput.